IL RILIEVO DI IMBARCAZIONI STORICHE - SLOMP, FRANCO; PENZO, GILBERTO (Archeomatica, 2012)
Historical craft's relief - The historical importance of a craft's relief,of which only a few copies for more built without a plan on paper, butonly with the method of the sixth, is an important cultural operationthat allows you to store and save forms, to study the hydrodynamiccharacteristics , compare with other similar boats and guide the subsequentwork of restoration or reconstruction of a twin hull.